Biochemical and Histopathological Assessment of Zinc Acetate-Induced Nephrotoxicity in Male Albino Rats - Mahmood Ali; Maha AL-Saffar AL-Saffar; Karam AL-mallah (Journal of Applied Veterinary Sciences, 2023)
Despite the fact that zinc is recognized to be less hazardous than other heavy metals, e.g. cadmium, lead, mercury and arsenic, it may cause acute and chronic toxicities in case of exposure to high doses. Aims of the study : To investigate biochemical and histopathological toxic effects of zinc acetate on rats kidney. Material and Methods: Twenty five healthy male albino rats were divided into five equal groups : Normal saline solution was given to the control group, groups 2,3,4, and 5 received zinc acetate (4,8,12, and 24mg/kg) respectively, all the treatment were given intraperitoneally once every other day for 3 consecutive weeks, for serum biochemical evaluation and renal histopathological assessment. Results : There was a significant increment in serum urea concentration in group 5 in comparison with other groups, but there was no significant difference in creatinine concentration between all of the groups (P ≤ 0.01), histopathological examination of kidney sections of rats of different groups revealed different lesions which were more severe at 4th and 5th groups. In conclusion: Subacute zinc acetate toxicity produce a dose-dependent significant effects on serum urea concentration in all the treated groups without any significant effects on creatinine concentration, this effect was reflected on renal histo-architecture which was more severe at 4th and 5th groups.